2017
DOI: 10.3399/bjgp17x692225
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in primary care: where are we now and where are we going?

Abstract: INTRODUCTIONAcute kidney injury (AKI) is defined as 'a clinical and biochemical diagnosis reflecting abrupt kidney dysfunction'. 1 AKI is graded on a scale of 1-3 based on the size of the creatinine increase from baseline. Higher AKI scores are associated with higher mortality, longer length of stay, and less renal recovery. 2 AKI complicates almost one in five hospital admissions and is associated with a 20-33% mortality rate, increased length of hospital stay, and an estimated annual cost to the NHS in Engla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A UK study has shown that the majority of patients who attend the ED have also consulted their primary care provider first [22]. However, in primary care there is often a lag time between decision to take blood tests (if such decision is made) and phlebotomy and between phlebotomy and the result being reviewed, usually by another clinician and this lag may have an effect on outcomes in infections associated AKI and sepsis [23]. Improvement in time to response to AKI alerts has been associated with decreased mortality in AKI 2&3 alerting in primary care [24] and prompt delivery of the sepsis bundle has been shown to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A UK study has shown that the majority of patients who attend the ED have also consulted their primary care provider first [22]. However, in primary care there is often a lag time between decision to take blood tests (if such decision is made) and phlebotomy and between phlebotomy and the result being reviewed, usually by another clinician and this lag may have an effect on outcomes in infections associated AKI and sepsis [23]. Improvement in time to response to AKI alerts has been associated with decreased mortality in AKI 2&3 alerting in primary care [24] and prompt delivery of the sepsis bundle has been shown to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, timely intervention with "sick day guidance" could be possible for patients using nephrotoxic drugs as it is a leading risk factor for CA-AKI. Thus, further work should be encouraged to generate evidence in this issue in which the patients are advised to avoid diuretics, non-steroidal antiinflammatory drugs, angiotensin II receptor blockers or angiotensin-converting enzyme inhibitors during acute illness [22].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Due to overloaded primary care services, efforts are desirable for the development of risk stratification models and monitoring of the health users aiming at effective actions and better Quality of Life (QoL) [3].…”
Section: Introductionmentioning
confidence: 99%